Development of Learning Media Based on E-Books and Quizz to Improve Student Learning Outcomes in Class X MA Roudlotut Tholibin Geger - Hasan, Moh.Fikri Haikal; Mariatun, Ika Lis (FKIP-Universitas Riau, 2024)
This study aims to intervene with teachers regarding E-book and Quizzizz-based learning media in class X economics subjects at MA Roudlotut Tholibin Geger. The development of learning materials this time uses the research model (ADDIE). Data collection techniques in this study were observation, test, questionnaire and interview. The research subjects were MA Roudlotut Tholibin class X students totaling 8 students. Based on the results of the study, it shows that the development of E-book and Quizizz-based learning media in the economics class X MA Roudlotut Tholibin can be said to be feasible to use in the learning process. The results of after the trial, the average score obtained by students who scored in the sufficient category (C) did not exist, students who scored in the good category (B) were 6 people, and students who scored in the excellent category (A) were 2 people. The average score obtained was 83.62 with a good category.